Obituary Alan John Flisher 16 April 1957 – 18 April 2010 - Foster, Don; Dawes, Andy (PINS-Psychology in Society, 2025)
We have lost a friend, a comrade, a superb teacher and academic, a highly accomplished social and medical scientist, a dedicated activist and a teacher, particularly in the sphere of mental health. He was also a devoted family man and leaves his long standing partner Mehrunisa and their nine year old twins, Khaleila and Adam. Alan died in Cape Town of leukaemia at the age of 53 years. He will be sorely missed. At the time of his death he held the Sue Strengmann Chair in Child Psychiatry and Mental Health at the University of Cape Town (UCT). All his formal qualifications – seven in all – were from UCT. He also held an Adjunct Professorship in health promotion at the University of Berger, Norway, and was Director of the Mental Health and Poverty Project at UCT.